Birds of the International Institute of Tropical Agriculture campus, a stronghold of avian diversity in the changing Ibadan area (Nigeria) over the last 50 years - Adeyanju, T.A.; Ottosson, U.; Adeyanju, T.E.; Omotoriogun, T.C.; Hall, P.; Manu, S.A.; Alabi, Tunrayo; Lameed, G.A.; Bown, D. (2014)
Data from a survey carried out between 2009 and 2013 of the bird species in the International Institute of Tropical Agriculture (IITA) campus, Ibadan, Nigeria, are compared with records from the area around Ibadan (including IITA) for the last 50 years. The IITA campus is an Important Bird Area (IBA) and includes a secondary dry semi-deciduous forest reserve of c. 360 ha, which is fenced and protected. The forested area is now being extended and enhanced by planting indigenous trees on degraded farm plots, and by enrichment planting in degraded areas of forest. In total, 398 bird species from at least 71 families are now recorded for the Ibadan area, of which 322 species have been recorded since 2002. The IBA holds at least 269 of these species (68 %) in 64 families, while the forest reserve holds c. 137 species. Seventy-five species were mist-netted in the IBA in our study. Twenty-five species plus 13 vagrants are new to the IBA and the Ibadan area in general, having not been detected prior to 2002. However, a minimum 68 species plus an additional 62 vagrant species reported in the Ibadan area by earlier studies have not been detected recently. We report an additional 29 biome-restricted species present in the Ibadan area (74 had been reported previously), 17 of which occur in the IBA. Diversity of some groups of large birds (e.g. Anatidae) has declined whereas many forest edge or generalist species (e.g. Double-spurred Francolin Francolinus bicalcaratus) have increased in abundance and range. Forest specialists, including many Pycnonotidae and Bucerotidae species, appear to have declined. The IITA campus, with its forest reserve, lakes and farm plots, is now an "island" IBA of great avifaunal diversity surrounded by a highly modified anthropogenic landscape unwelcoming for many of the birds that formerly inhabited the area.